Properties of cold bonded quarry dust coarse aggregates and its use in concrete. (September 2015) - Thomas, Job; Harilal, B.
Abstract: In this study, artificial coarse aggregates are prepared by a cold bonding technique. The waste materials, namely, fly ash and quarry dust, are used for the preparation of the cold bonded artificial aggregate. Portland cement is used as the binder material. The independent variables considered for the preparation of the artificial aggregate are cement and fly ash contents. The properties of the artificial aggregate are determined and regression models are proposed for predicting these properties. The strength and workability of concrete containing artificial aggregate is determined. The slump loss of concrete containing artificial aggregate is found to be gradual. The concretes with strengths of up to 30 MPa is prepared using artificial aggregates. The study promotes the use of waste material and supports sustainable construction practices.